Seroprevalence and associated factors of Hepatitis B virus among diabetic adult patients attending at Haramaya General Hospital, Eastern Ethiopia - Abdi, Adnan; Ayele, Firayad; Mohammed, Jemal; Ayana, Desalegn Admassu (Frontiers in Public Health, 2025)
BackgroundHepatitis B virus (HBV) infection and diabetes mellitus are both significant public health concerns that substantially impact global morbidity and death. However, there is currently limited information available on the prevalence of HBV infection among diabetic patients in eastern Ethiopia. Therefore, this study aimed to determine the seroprevalence and associated factors of the Hepatitis B virus among diabetic adult patients at Haramaya General Hospital in Eastern Ethiopia from August 8 to August 30, 2021.MethodsAn institution-based cross-sectional study was done among 365 diabetic patients. Study participants were chosen using a consecutive sampling technique. Data on sociodemographic characteristics and other associated factors were collected using a structured questionnaire. A blood sample was drawn from each participant, and the serum was separated and tested for HBsAg status using the Rapid Test Kit (ACON, USA). The data was entered into Epi Data version 4.6 software and analysed using SPSS version 25. Bivariate and multivariable logistic regression analyses were performed to examine the association between the outcome variable and predictor factors. A p-value less than 0.05 was considered statistically significant.ResultsA total of 365 individuals with diabetes took part in this study. The overall seroprevalence of hepatitis B surface antigen among these patients was 7.4% (95% CI = 4.71–10.08). Among the total of 365, about 243 individuals (66.3%) were male, and the participants had a mean age of 42.24 ± 10.2 years. The only significant risk factor for Hepatitis B virus (HBV) coinfection among the diabetic patients was having multiple sexual partners [AOR = 2.92, 95% CI: 1.2–7.08].ConclusionThis study found an intermediate prevalence of Hepatitis B virus (HBV) infection among people with diabetes. Multiple sexual partners were strongly associated with an increased likelihood of HBV infection. Based on these findings, it is recommended to implement routine HBsAg screening for diabetic patients during regular medical visits to enable earlier detection and timely treatment. The government also should increase vaccination coverage for diabetic patients. Healthcare facilities, regional authorities, and experts should also teach diabetes patients about hepatitis B transmission routes and prevention strategies, with an emphasis on modifiable variables.